Development of Board Game Media in Art Culture and Craft Learning at 5th Grade of Elementary School - Maulana, Puja; Asmarani, Ratih (IJPSE : Indonesian Journal of Primary Science Education, 2021)
Indonesia has a variety of cultures including traditional dances that students must know and which need to be socialized in learning. This socialization is carried out through education that is packaged as attractively as possible, namely media in the form of games (board game), especially for students. This study aims to introduce and memorize the dance culture of Indonesia in fifth grade at the elementary school level. To find out how the process of media development and how the quality of the media. This research is a type of ADDIE model research proposed by Tegeh which consists of four stages, includes analyze, design, implementation, and evaluation stage. The research subjects were fifth grade elementary school students in the academic year 2021/2022, based on field trials the results of expert validity research were in the very valid category with an overall average of 89%. The results of these student responses show a total score of 47 out of a maximum total score of 52. After being analyzed and presented as a percentage, the score is 90% with a very valid category. Based on field trials, researcher conducted tests on students with the results of classical learning completeness as much as 86%. Based on the results of data analysis in general, it can be concluded that SBdP learning using the Board Game media that has been developed greatly supports the learning process. With this, it can also be seen from the number of students who have completed the trial test on the material about traditional dance in Indonesia.